A Study on the First‐Derivative Output Properties of GaN Static Induction Transistor with Submicrometer Fin Width. Issue 2 (19th November 2019) - Chun, Jaeyi; Li, Siwei; Malakoutian, Mohamadali; Ji, Dong; Chowdhury, Srabanti
Abstract : The first derivative of output curves of a Schottky‐junction vertical channel GaN static induction transistor (SIT) with a submicrometer‐sized fin is studied to understand its fundamental electrical properties. It is found that the derivative of output curves increases with the increase in drain voltage ( V ds ) in ohmic region because of the raised potential minima in the channel, which is not seen in SITs with a relatively long fin width. The influence of the gate voltages ( V gs ) and V ds on electric potential in the channel is demonstrated by evaluating the contribution of V gs and V ds, expressed through two coefficients α and β . The ratio of α to β increases up to 31.1 from 16.3 with decrease in the fin width from 0.9 to 0.5 μm, showing a higher dependency of the potential minima on V gs and the fin width. The voltage gain expressed by α / β is 14.9 dB for the GaN SIT with a fin width of 0.5 μm. Abstract : The fundamental electrical properties of a Schottky‐junction vertical channel GaN static induction transistor, based on the analysis of the first derivative of its output curve, are discussed. The results cover the unique properties of conduction mechanism in a submicrometer channel and the device electrostatics governed by the external biases to control the performance of the device.